Catheter-related Mycobacterium fortuitum Bloodstream Infection: Rapid Identification Using MALDI-TOF Mass Spectrometry - Artacho-Reinoso, M. J.; Olbrich, P.; Solano-Paéz, P.; Ybot-Gonzalez, P.; Lepe, J. A.; Neth, O.; Aznar, J. (Klinische Pädiatrie, 2014)
We present the case of a 6-year-old boy diagnosed with stage III mediastinal Non Hodgkin Lymphoblastic T cell Lymphoma who suffered from catheter-related bloodstream infection (CRBI) due to Mycobacterium fortuitum whilst receiving chemotherapy. Isolation of this rare pathogen was done directly from blood culture and identification was made rapidly within 48 h using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry as well as specific polymerase chain reaction (PCR)-reverse hybridization method. This allowed prompt directed antibiotic therapy apart from central venous catheter removal and resulted in an excellent clinical response. This case highlights the potential benefit of using MALDI-TOF mass spectrometry, a fast, cost-effective and precise methodology, in the diagnosis and subsequent management of invasive bacterial infection.
Keywords: Mycobacterium fortuitum; childhood; catheter related infection; MALDI TOF; oncology